The Science of Obesity Management: An Endocrine Society Scientific Statement - Bray, George A; Heisel, William E; Afshin, Ashkan; Jensen, Michael D; Dietz, William H; Long, Michael; Kushner, Robert F; Daniels, Stephen R; Wadden, Thomas A; Tsai, Adam G; Hu, Frank B; Jakicic, John M; et al. (Endocrine reviews, 2018)
Abstract The prevalence of obesity, measured by body mass index, has risen to unacceptable levels in both men and women in the United States and worldwide with resultant hazardous health implications. Genetic, environmental, and behavioral factors influence the development of obesity, and both the general public and health professionals stigmatize those who suffer from the disease. Obesity is associated with and contributes to a shortened life span, type 2 diabetes mellitus, cardiovascular disease, some cancers, kidney disease, obstructive sleep apnea, gout, osteoarthritis, and hepatobiliary disease, among others. Weight loss reduces all of these diseases in a dose-related manner-the more weight lost, the better the outcome. The phenotype of "medically healthy obesity" appears to be a transient state that progresses over time to an unhealthy phenotype, especially in children and adolescents. Weight loss is best achieved by reducing energy intake and increasing energy expenditure. Programs that are effective for weight loss include peer-reviewed and approved lifestyle modification programs, diets, commercial weight-loss programs, exercise programs, medications, and surgery. Over-the-counter herbal preparations that some patients use to treat obesity have limited, if any, data documenting their efficacy or safety, and there are few regulatory requirements. Weight regain is expected in all patients, especially when treatment is discontinued. When making treatment decisions, clinicians should consider body fat distribution and individual health risks in addition to body mass index. This Scientific Statement critically reviews the definition of obesity, providing a list of assessment methods, obesity-related diseases, and prevention measures.